2012
DOI: 10.1128/iai.05918-11
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Chinchilla Model for Nasopharyngeal Colonization To Study Gene Expression by Moraxella catarrhalis

Abstract: Young adult chinchillas were atraumatically inoculated with Moraxella catarrhalis via the nasal route. Detailed histopathologic examination of nasopharyngeal tissues isolated from these M. catarrhalis-infected animals revealed the presence of significant inflammation within the epithelium. Absence of similar histopathologic findings in sham-inoculated animals confirmed that M. catarrhalis was exposed to significant host-derived factors in this environment. Twenty-four hours after inoculation, viable M. catarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 66 publications
2
34
1
Order By: Relevance
“…M. catarrhalis is a strict human pathogen, and a workable animal model for studying M. catarrhalis pathogenesis remains to be developed. Chinchilla nasopharyngeal colonization studies showed that M. catarrhalis colonized the nasopharynxes of chinchillas without apparent disease symptoms (4,32,43). To investigate whether bacterium-generated NO· could be involved in pathogenesis, we optimized an in vitro system using HBE cells as the host in bacterium-host cell cocultures.…”
Section: Resultsmentioning
confidence: 99%
“…M. catarrhalis is a strict human pathogen, and a workable animal model for studying M. catarrhalis pathogenesis remains to be developed. Chinchilla nasopharyngeal colonization studies showed that M. catarrhalis colonized the nasopharynxes of chinchillas without apparent disease symptoms (4,32,43). To investigate whether bacterium-generated NO· could be involved in pathogenesis, we optimized an in vitro system using HBE cells as the host in bacterium-host cell cocultures.…”
Section: Resultsmentioning
confidence: 99%
“…transcriptional activators and repressors (77)(78)(79). Examination of data from a previous study that identified M. catarrhalis genes whose expression was upregulated when broth-grown bacteria were inoculated into the chinchilla nasopharynx (21) showed that there was little or no change in the level of mesR transcription, even though the levels of lipA and lipB transcripts increased approximately 4-fold and 1.5-fold, respectively. In M. catarrhalis bacteria that attached to human bronchial epithelial cells in vitro (80), there were very modest (i.e., 1.4-to 1.5-fold) increases in mesR, lipA, and lipB transcription levels.…”
Section: Discussionmentioning
confidence: 99%
“…A BLAST search for lysozyme proteins revealed that the chinchilla (Chinchilla lanigera) genome encodes both a predicted c-type lysozyme and a predicted g-type lysozyme. The potential expression of two different lysozymes by this rodent makes it problematic to use the chinchilla model for nasopharyngeal colonization by M. catarrhalis (21,104) to evaluate the different lysozyme inhibitor mutants constructed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations